MANAGEMENT OF JAWA POS MEDIA CONVERGENCE IN THE DIGITAL ERA - Fuada, Sofia Nurul; Setianingrum, Vinda Maya (The Commercium, 2024)
This research aims to determine the media convergence management implemented by Jawa Pos in the digital era with a research focus on the policies taken by the Editors in Chief from three Jawa Pos business units including: Jawa Pos Koran, JawaPos.com, and JawaPos TV in operational convergence management media. Management is a benchmark for how Jawa Pos can maintain itself in the current digital era, especially by integrating the three business units so that they can be multiplatform perfectly. The type of research used in this research is qualitative descriptive research with a constructivist paradigm to review the reality that is happening. Data collection was carried out through interviews with sources, observation and documentation. In reviewing the implementation of Jawa Pos convergence management, researchers used the management theory of George Robert Terry POAC (Planning, Organizing, Actuating, Controlling) and the Niche theory by Dimmick and Rothenbuhler. From the research results, the three Chief Editors of the Jawa Pos business unit created a 3M policy (mutimedia, multiplatform and multichannel) and a policy for changing the organizational structure in managing media convergence to be able to maintain its existence in the digital era. This policy resulted in Jawa Pos increasing the diversity of its news programs, as well as cutting HR costs.